Unspoken cycles: A qualitative study exploring the lived experiences of women’s menstruation in the urban informal settlements of Bangladesh - Marufa Alam; Md. Al-Mamun (PLoS ONE, 2026)
Background Menstrual health and hygiene (MHH) is a critical component of public health and gender equity. However, limited research has explored the everyday experiences of women and adolescent girls managing menstruation within the constrained environment of urban informal settlements. This study explores the lived experiences of menstruation among women and girls in the Khulna Railway Slum in Bangladesh. Methods Guided by a Feminist Political Ecology framework, this qualitative study employed a combined inductive and deductive thematic approach. Data were collected between September and October 2025 through in-depth interviews with 18 women and adolescent girls aged 15–45 years living in urban informal settlements in Khulna. Five key informant interviews were also conducted with relevant stakeholders. Data were analyzed thematically using both pre-defined conceptual domains and emergent codes. Findings Findings revealed that menstrual experiences are shaped by three interrelated conceptual domains: structural-environmental constraints, socio-cultural stigma, and gendered inequities in access to resources. Inadequate WASH facilities, poor waste management, and lack of affordable menstrual products hinder safe and dignified menstrual practices. Stigma and taboos reinforced shame, exclusion, and silence, while gendered inequalities limited autonomy and resource access, especially among adolescents. Conclusion The study highlights menstruation as a socially and structurally shaped experience influenced by infrastructural constraints, cultural norms, and gendered inequalities. It contributes to scholarship on menstrual health by emphasizing the need to address menstrual inequities as part of broader efforts to improve gender equity and WASH services in urban informal settlement.